IMPLEMENTASI NILAI-NILAI MORAL PAPASENG SEBAGAI KEARIFAN LOKAL BUDAYA BUGIS DALAM BIMBINGAN DAN KONSELING [IMPLEMENTATION OF PAPASENG MORAL VALUES AS LOCAL WISDOM OF BUGIS CULTURE IN GUIDANCE AND COUNSELING] - A, Zulkifli; Estuningrum, E; Lessy, Zulkipli (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2023)
This study discusses the implementation of papaseng moral values as local wisdom of Bugis culture in guidance and counseling. The research method used is a literature study. The results of this study are the implementation of Papaseng's moral values into guidance and counseling services, namely the moral values of honesty and mutual cooperation. Papaseng is a message or advice from parents in the form of ideas, ideas, thoughts, and opinions about what is good and what is bad. The types of guidance and counseling services used in implementing local wisdom values of Bugis culture are individual guidance and counseling as well as counseling and group counseling.